A Study on the Coordination of Urban Traffic Control and Traffic Assignment - ZhaoWei Qu; Yan Xing; XianMin Song; YuZhou Duan; Fulu Wei (Discrete Dynamics in Nature and Society)
The interactions between signal setting and traffic assignment can directly affect the urban road network efficiency. In order to improve the coordination of signal setting with traffic assignment, this paper created a traffic control algorithm considering traffic assignment; meanwhile, the link impedance function and the route choice function were introduced into this paper to study the user's route choice and the road network flow distribution. Then based on the above research, we created a system utility value model. Finally through the VISSIM software to simulate the test network, we verified the superiority of the coordination algorithm and the model and gave the optimal flow of the road network.